Pathogens that infect mammalian cells via sulfonated glycosaminoglycans - Morris, Jessica S.; Dawson, Paul A. (Frontiers in Cellular and Infection Microbiology, 2025)
Sulfonated glycosaminoglycans, such as heparan sulfate and dermatan sulfate, form major components of the cell surface and extracellular matrix, and display vital roles in mammalian physiology, including growth and development. The identification of specific binding to different glycosaminoglycans by a variety of pathogens has led to increased interest in this mechanism for understanding infection. Over the past four decades there have been more than 300 studies on various pathogens that utilize glycosaminoglycans in their infection process. Currently, no articles have collated all known pathogens that use this process. So it is timely that this article provides an overview of all known pathogens that use glycosaminoglycans to enhance their binding and/or infection in human cells. This was done by using the search terms “sulfate/sulphate” “pathogen”, “virus”, “bacteria”, “parasite”, “infection” and “glycosaminoglycans” to curate peer-reviewed and relevant original research articles from PubMed. This search found that glycosaminoglycans are used in the infection process for 59 viruses, 28 bacteria, and 8 other pathogens (i.e. parasitic protozoa, prions). These findings highlight the conserved and widespread use of glycosaminoglycans for enhancing pathogen infection. In addition, the curated list of pathogens in this study provides a resource for future studies to consider potential therapeutic approaches for targeted disruption of the interaction between pathogens and glycosaminoglycans.